Collaboration between general dental practitioners and dental hygienists: a qualitative study - Joost C. L. den Boer; Brigitte A. F. M. van Dam; Wil J. M. van der Sanden; Josef J. M. Bruers (BMC, 2022)
Abstract Background Influenced by governmental measures, collaboration in oral health care practices in the Netherlands has increased in recent decades. Previous studies on this subject have mainly concerned the composition of the staff or have been normative rather than descriptive. Based on the existing literature, four aspects were expected to be of significant influence on the collaboration on oral health care practices: goals, leadership, the allocation of tasks and responsibilities and formalization. Methods The aim of this study was to describe a classification of collaboration between general dental practitioners and dental hygienists within oral health care practices in the Netherlands. Eighteen semi-structured face-to-face interviews were conducted in nine oral health care practices, which differed with regard to both practice characteristics and characteristics of the principal general dental practitioner. In all practices, the principal general dental practitioner and one dental hygienist were consulted. The interviews were conducted in the practices of the respondents and were held between October 2019 and July 2020. The interviews were analyzed through theoretical thematic analysis using Microsoft Word 2010 and Atlas.ti 8. Three researchers coded and analyzed three practices, and discussed their results. Based on their mutual conclusions, one researcher analysed all practices. The final results were reviewed and approved by the other two researchers. Results Different factors influencing the collaboration between general dental practitioners and dental hygienist in the Netherlands were found. The most important factors seemed to be leadership style and goals for collaboration. Leadership style varied from very directive to very supportive and seemed to be connected to the allocation of responsibilities. Goals for collaboration varied from predominantly patient-related to mostly practice-related. Formalization appeared to be more present in larger practices and practices that are affiliated to a dental chain. Conclusions Based on leadership style and goals for collaboration, a classification was identified. This classification is recommended as a starting point for further research on directive and supportive leadership in oral health care practices.